Evaluation of probiotic potential, safety assessment and whole genome sequencing of Lactiplantibacillus plantarum strain MOVIN isolated from toddy sample - Vijayaganapathi, A.; Mohanasrinivasan, V. (Frontiers in Microbiology, 2025)
IntroductionToddy, an alcoholic drink produced through natural fermentation, is a significant reservoir of probiotic microorganisms. Probiotics are increasingly studied for their beneficial effects in managing gastrointestinal disorders, enhancing immune responses, and promoting overall health. Lactiplantibacillus plantarum is a well-known probiotic strain as it possesses gastrointestinal survival, antimicrobial activity, and adaptability to various environmental factors. This study aims to isolate and characterize probiotic bacteria from toddy samples, with a focus on their bioactive and genomic attributes.MethodsTwenty bacterial strains were isolated from toddy samples and subjected to preliminary biochemical screening. Of these, 17 isolates were selected for further screening of antibacterial activity against foodborne pathogens. These isolates were also evaluated for probiotic traits such as auto-aggregation, hydrophobicity, tolerance to bile, acid, and NaCl. Antibiotic susceptibility was assessed against nine antibiotics. The most promising isolate was subjected to whole-genome sequencing, followed by in silico genomic analysis using BAGEL4, antiSMASH, and the KEGG automatic annotation server.ResultsAmong the 17 selected isolates, VITVTD-3, VITVTO-5, and VITVH-5 exhibited inhibitory effects against all tested food-borne pathogens. These isolates also showed moderate levels of auto-aggregation and hydrophobicity, along with the ability to withstand bile salts, acidic pH, and high salt concentrations. Antibiotic profiling revealed resistance to vancomycin in all three isolates. Antioxidant and haemolytic activity assays further supported their probiotic potential. Of these, VITVTD-3 demonstrated the most favourable combination of probiotic attributes. Whole-genome sequencing revealed that this isolate corresponds to Lactiplantibacillus plantarum strain MOVIN, possessing a genome size of 3.16 Mb and a GC content of 44.4%. Genomic analysis revealed the presence of a plantaricin operon and multiple bacteriocin gene clusters. KEGG annotation predicted 5,599 genes involved in 23 different metabolic pathways.DiscussionThe findings confirm that Lactiplantibacillus plantarum MOVIN exhibits strong probiotic characteristics, supported by phenotypic, functional, and genomic evidence. The presence of bacteriocin biosynthesis genes, along with the ability to inhibit pathogenic microorganisms and survive gastrointestinal conditions, highlights its suitability for probiotic applications. Further functional studies and safety evaluations are warranted to explore its potential use in food or therapeutic formulations.